Perbandingan Certainty Factor dan Dempster Shafer dalam Sistem Pakar Diagnosis Penyakit Tanaman Padi Kerjasama dengan Petani: Comparison of Certainty Factor and Dempster Shafer in an Expert System for Rice Diagnosis in Cooperation With Farmers - Nidhom Ichtira; I Gede Pasek Suta Wijaya; Arik Aranta (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2023)
Rice is the staple food of the people in West Lombok. However, rice plants are susceptible to disease from pests, fungi and unfavorable environments. This study was constructed to compare the performance of the Dempster Shafer and Certainty Factor methods in an expert system for diagnosing rice plant diseases based on the knowledge of 3 experts. From the accuracy test performed, it was found that the accuracy value of the system using the Dempster Shafer method was 81.11% while using the Certainty Factor method an accuracy value was 69%, so it can be concluded that the expert system for diagnosing rice plant diseases using the Dempster Shafer method is more accurate than using Certainty Factor method. From the MOS test carried out, using the Dempster Shafer method and obtained an average result of 4.2 while using the Certainty Factor method obtained an average result of 4.63, so it can be concluded that the system with the Certainty Factor method is easier and more interesting to use even though the accuracy value is lower.